Functional Status Geriatric Scores: Single-Handed Tools for 30-Day Mortality Risk After Hip Fracture - da Casa C; Pablos-Hernández C; González-Ramírez A; Blanco JF (Clinical Interventions in Aging, 2021)
Carmen da Casa,1 Carmen Pablos-Hernández,1,2 Alfonso González-Ramírez,1,2 Juan F Blanco1,3 1Instituto de investigación biomédica de Salamanca (IBSAL), Salamanca, Spain; 2Othogeriatric Unit, Hospital Universitario de Salamanca, Salamanca, Spain; 3Trauma and Orthopedic Surgery Department, Hospital Universitario de Salamanca, Salamanca, SpainCorrespondence: Juan F BlancoTrauma and Orthopedic Surgery Department, Hospital Universitario de Salamanca, Paseo San Vicente, 58-182, Salamanca, 37007, SpainTel +34 923291100 ext. 55390Email jfblanco@usal.esBackground: The 30-day mortality rate after hip fracture surgery has been considered as an indirect indicator of the quality of care. This work aims to appraise the Barthel Index, Katz Index, Lawton-Brody Index, and Physical Red Cross Scale registered in the Comprehensive Geriatric Assessment at admission on the of 30-day death probability after hip fracture surgery.Methods: Prospective study including 899 hip fracture patients over 65. Bed-ridden, non-surgically treated patients, and high energy trauma or tumoral etiology fractures were excluded. Variables distribution were assessed by χ2, U-Mann Whitney and we performed binary logistic regression and equal tailed Jeffreys 95% CI for risk assessment. P< 0.05 was considered statistically significant.Results: We noted a 30-day mortality rate of 5.9%. We related Barthel Index (OR=0.986 [0.975– 0.996], p=0.010), Katz Index (OR=1.254 [1.089– 1.444], p=0.002), Lawton-Brody Index (OR=0.885 [0.788– 0.992], p=0.037), and Physical Red Cross Scale (OR=1.483 [1.094– 2.011], p=0.011) with the 30-day mortality of patients after hip fracture surgery. We also validated the Barthel Index inflection point (0– 55) (ORBI(0– 55)=2.428 [1.379– 4.275], p=0.002) and Katz Index inflection point (A-B) (ORKI(A-B)=0.493 [0.273– 0.891], p=0.019) for the assessment of the highest risked patients.Conclusion: The geriatric functional status scores would be useful multifunctional and standalone tools in the assessment of hip fracture patients as singly predictors of 30-day mortality.Keywords: comprehensive geriatric assessment, hip fracture, mortality, geriatric scores